Primary Accounting of Production Costs in Agricultural Holdings and its Improvement: Array - Chira, Tatiana (Journal of Danubian Studies and Research, 2021)
A well-founded organization of cost accounting in agriculture requires in many respects a revision of the principles of reflecting economic facts in primary accounting in strict accordance with the requirements of modern business systems and modern conditions for the use of the necessary spectrum in modern technologies. Resources. Currently, the unification of information carriers and the rationalization of the content of documents are of paramount importance - the actions, we believe, will generate the development of standard forms, updated with a simultaneous reduction in the number of mandatory elements to reflect similar operations and adapt to them. Requirements for automated processing.